2015
DOI: 10.1016/j.schres.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motivational salience processing during the early stages of psychosis

Abstract: The changes in adaptive motivational salience processing during psychosis development reveal neurofunctional abnormalities in the somatosensory and premotor cortex. Antipsychotic medication seems to modify hemodynamic responses in the anterior cingulate and insula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 65 publications
4
65
2
Order By: Relevance
“…[15][16][17][18] Other studies including patients with broadly defined first-episode psychosis (not restricted to schizophrenia and schizophreniform disorder) or individuals at-risk for psychosis did not report any group differences, but focused more on the relationship with symptom expression. [19][20][21][22][23] This work supports the idea that on a group level reduced activation of the striatum may be more strongly related to schizophrenia or chronic forms of psychosis than to psychotic disorders in general. Importantly, these divergent findings highlight the importance of using dimensional approaches to investigate the neural basis of psychosis rather than restricting research to group differences.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…[15][16][17][18] Other studies including patients with broadly defined first-episode psychosis (not restricted to schizophrenia and schizophreniform disorder) or individuals at-risk for psychosis did not report any group differences, but focused more on the relationship with symptom expression. [19][20][21][22][23] This work supports the idea that on a group level reduced activation of the striatum may be more strongly related to schizophrenia or chronic forms of psychosis than to psychotic disorders in general. Importantly, these divergent findings highlight the importance of using dimensional approaches to investigate the neural basis of psychosis rather than restricting research to group differences.…”
Section: Introductionsupporting
confidence: 80%
“…19,53 At the group level, we found no differences between HCs and individuals with SPT or first-episode psychosis in VS activation, which is consistent with previous results in broadly defined FEP patients and individuals at-risk for psychosis. [19][20][21][22] In contrast, there is now meta-analytic support for reduced VS activation in patients with established schizophrenia, 24 but results on the individual study level are very inconsistent. 15,16,23,25,31,35,59,62,63 These mixed findings support the notion that striatal alterations in psychosis do not solely consist of hypo-activation but vary between different stages (early vs chronic) and different forms of psychosis (schizophrenia vs non-schizophrenia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 These 3 fMRI studies together show local activity changes mainly in the VS, insula and ACC in patients with FEP during reward prediction 4,5,14 as well as alterations in these regions induced by antipsychotic medication. 11,14 One previous fMRI study in unmedicated patients with schizophrenia showed reduced connectivity between the prefrontal cortex and the VS during reward processing.…”
Section: Introductionmentioning
confidence: 93%
“…11 Although not speci cally during reward processing, a recent resting-state fMRI study in patients J Psychiatry Neurosci 2016;41 (6) with FEP also showed that atypical antipsychotics increased functional connectivity between striatal regions, the ACC and right anterior insula, 12 which correlated positively with symptom improvement. Using the Salience Attribution Task (SAT), 13 Smieskova and colleagues 14 recently reported that compared with controls patients with FEP showed reduced right insula activity in response to high-versus low-probability reward cues. Furthermore, the right insula and ACC activity was negatively correlated with the severity of hallucinations in unmedi cated patients.…”
Section: Introductionmentioning
confidence: 99%